Análisis de la vulnerabilidad en el sistema de alcantarillado del cantón Echeandía - Rueda Ramos, Alison Brishit (2021)
The investigation entitled "Analysis of the vulnerability in the sewerage system of the Echeandía canton", was developed in the Echeandía canton belonging to the Bolívar province, due to its geographical location as it presents great exposure to a series of natural hazards which puts at risk the functioning of vital networks. Through the application of the “Guide to implement the vulnerability analysis at the cantonal level proposed by the National Secretariat for Risk Management (SNGR) and the United Nations Development Program (UNDP), 2011, it was determined that the Echeandía canton It is exposed to a medium vulnerability in terms of earthquakes with 43% of the territory exposed, to landslides with a 52% exposure of the territory and a high vulnerability to floods with 65.15% exposure of its territory. Likewise, physical vulnerability was determined by evaluating indicators of hydraulic operation, current state, age, maintenance, construction materials and design and construction standards, where a score of 85/100 for earthquakes, 90/100 for floods was obtained. and 87.5 / 100 for landslides, values that give them a high level of vulnerability. In the same way, functional vulnerability was determined by evaluating the factors: service coverage, obtaining that the sewerage coverage of the Echeandía canton is 48%, conferring a high functional vulnerability (due to the fact that less than 50% of the canton has this service) and the intervention capacity factor also obtained a high vulnerability due to the fact that the responsible institution has qualified personnel but without equipment for the development of the different technical and specific activities that the xxi sewerage system requires. The modeling of sanitary and storm sewers was also carried out using the CYPE software, which allowed defining that in relation to the fecal load there are 27 points with a circulation speed of less than 0.5 m / s and in relation to the rain load, 19 points were identified. with circulation less than 0.5 m / s, which denotes a minimum runoff that can cause accumulations of bodies of water and sediments that expose the different sections of the sewer system to collapse.